Experimental determination of proton-induced cross-sections on natural zirconium - Khandaker, Mayeen Uddin; Lee, Y.O.; Kim, K.; Lee, M.W.; Kim, K.S.; Kim, G.N.; Cho, Y.S. (Elsevier, 2009)
We measured cross-sections for the formation of (86g.87m.87g)Y, (88.89g)Zr, and (90.92m)Nb radionuclides for proton-induced reactions on natural zirconium by using a conventional stacked-foil activation technique in the energy range between I and 40MeV at the MC-50 cyclotron of the Korea Institute of Radiological and Medical Science. We compared the measured data with the available literature data and the theoretical calculation by the model codes TALYS and ALICE-IPPE. We also deduced the integral yields for thick targets from the measured cross-sections of the produced radionuclides. The optimum production possibility of the medically important (89g)Zr and (86)Y radionuclides were discussed elaborately. (c) 2009 Elsevier Ltd. All rights reserved.